1998
DOI: 10.1098/rspb.1998.0492
|View full text |Cite
|
Sign up to set email alerts
|

Speciation durations and Pleistocene effects on vertebrate phylogeography

Abstract: An approach applied previously to avian biotas is extended in this paper to other vertebrate classes to evaluate Pleistocene phylogeographic e¡ects and to estimate temporal spans of the speciation process (speciation durations) from mitochondrial (mt) DNA data on extant taxa. Provisional molecular clocks are used to date population separations and to bracket estimates of speciation durations between minimum and maximum values inferred from genetic distances between, respectively, extant pairs of intraspeci¢c p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
386
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(419 citation statements)
references
References 27 publications
26
386
1
6
Order By: Relevance
“…First, Britain has been subject to frequent glaciation periods during which most species would have been displaced further south. Moreover, speciation in Britain could only have occurred during the interglacial periods and these were typically much shorter, approximately 25,000 years (Adams et al 1999), than the time typically required for avian speciation, which has been estimated at between 250,000 and two million years (Avise et al 1998;Johnson & Cicero 2004). Second, most species breeding in Britain have large geographic ranges covering Europe, and often parts of Asia and/or Africa (Gregory & Blackburn 1998); it would be rather remarkable if the majority of these species evolved in the same small area of their distribution.…”
Section: Resultsmentioning
confidence: 99%
“…First, Britain has been subject to frequent glaciation periods during which most species would have been displaced further south. Moreover, speciation in Britain could only have occurred during the interglacial periods and these were typically much shorter, approximately 25,000 years (Adams et al 1999), than the time typically required for avian speciation, which has been estimated at between 250,000 and two million years (Avise et al 1998;Johnson & Cicero 2004). Second, most species breeding in Britain have large geographic ranges covering Europe, and often parts of Asia and/or Africa (Gregory & Blackburn 1998); it would be rather remarkable if the majority of these species evolved in the same small area of their distribution.…”
Section: Resultsmentioning
confidence: 99%
“…This period is characterized by repeated glaciation events, leading to drastic changes in the vegetation composition within different biomes. Avise et al (1998) reported that among major intraspecific phylogroups identified in the mammals, herpetofauna and fishes, population divergence times fall within the Pleistocene.…”
Section: Discussionmentioning
confidence: 99%
“…The level of genetic divergence for H. polygyrus cyt b gene was estimated to 3.5-3.7% K 2 P (Kimura' s two parameter distance estimator) distance per million years. Genetic divergence was estimated in K 2 P distances to allow comparison with most of the published phylogeographic studies (e.g., see Avise et al, 1998), and was corrected for ancestral mtDNA polymorphism (Edwards and Beerli, 2000). This estimation was used in this study to infer the isolation epoch of the new parasite genetic lineages (Polish, Turkish and Moroccan).…”
Section: Estimation Of Divergence Time Of Parasite Lineagesmentioning
confidence: 99%